Settlement of Investment Disputes Based on the Bilateral Investment Treaty through Arbitration of the International Centre for Settlement of Investment Disputes (Case Study of Rafat Ali Rizvi vs. the Republic of Indonesia) - Saputra, Ade Rizki; Gunati, Mira; Faisal, Ryan; Mardiansah, Songgi; Wiradirja, Imas Rosidawati; Pranadita, Nugraha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses foreign investment disputes involving Indonesia in international arbitration forums, particularly under the jurisdiction of ICSID (International Centre for Settlement of Investment Disputes). The main focus of this study is on the interpretation of the provisions of Article 2 paragraph (1) in the Indonesia-UK Bilateral Investment Treaty (BIT), which regulates the conditions for the entry of foreign investment in Indonesia. In the Rafat Ali Rizvi case, the arbitration panel decided that the process of entering investment that does not comply with the provisions of the Foreign Investment Law (UU PMA) cannot be included in the scope of the BIT. This study provides important recommendations for Indonesia in re-evaluating the provisions in each BIT involving Indonesia, as well as conducting further studies on ICSID arbitration decisions to understand the interpretation of BIT articles related to jurisdiction and the subject matter. Thus, this study aims to strengthen Indonesia's position in facing investment disputes at the international level